STRATEGI PENGEMBANGAN SITUS PURBAKALA PATIAYAM SEBAGAI ASET PARIWISATA KABUPATEN KUDUS - Dea Martha; Tri Yuniningsih; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Situs Patiayam, is a new tourism destination in Kabupaten Kudus, that having lots of potential to be developed. But, the condition is not comparable yet, with the potencies. The questions are; what internal and external factors, supporting and inhibiting factors, success factors, and how regional Government Kabupaten Kudus to develop the potencies of Situs Patiayam. This research aims to identify internal and external factors, supporting and inhibiting factors, success factors, and analyze how Regional Government Kabupaten Kudus, to develop the potencies of Situs Patiayam. Using theory of strategic management, this research using SWOT Analysis to identify the strengths, weaknesses, opportunities, and threats, in strategic circle. This research is a qualitative descriptive type of research. Strategic management is important to do, and needed by departement to plan the program. The result shows that there are eight issues, in the process to developing Situs Patiayam. After using Litmus test measurement to evaluate the strategic issues, the two most strategic issues can be found. It is increasing cooperation with investors, also improving quality and variation of facilities in this tourism destination.